Service quality: evaluation on transaction services in Tabung Haji Banda Kaba, Melaka / Mohammad Ariff Ibrahim - Ibrahim, Mohammad Ariff (Faculty of Business and Management, 2006)
Nowadays service quality is often very difficult to manage, for variety of reasons. Managing service quality require knowing exactly what customers want, designing services to meet their needs and measuring customer satisfaction. Understanding and effectively managing service quality is critically important for the creation and maintenance of competitive advantage. In this context, this study mainly focuses on the service quality; evaluation on transaction services in Tabung Haji (TH) Banda Kaba, Melaka. It focused on the factors that influence service quality at TH. It is also to identify the types of problems which have been experienced by the depositors when making transaction services at TH and also to identify the elements of transaction services that can influence customer satisfaction. In order to achieve high standard of excellences and also service quality, it is important for Tabung Haji to build a long-term relationship with their customers to make them loyal with the organization. In this research, the researcher chooses exploratory as the research design in order to achieve the research objectives and to define the problems more precisely. Convenience sampling (non-probability sampling technique) is used since the researcher does not use chance selection procedures and the selection of respondents can be obtained easily. The study was carried at Tabung Haji Banda Kaba, Melaka and the respondents came from Central Melaka District. Based on this study, some suggestions have been recommended to TH and such information will definitely assist TH in further providing and maintaining service quality as to gives positive perceptions by the customers.